Chromosome 1q21.2 and additional loci influence risk of spontaneous coronary artery dissection and myocardial infarction - Jacqueline Saw (Nature Portfolio, 2020)
Spontaneous coronary artery dissection (SCAD) is a cause of myocardial infarction Here, the authors present a genome-wide association study of SCAD, finding an association at 1q21.2 which potentially affects expression of ADAMTSL4.